Kepemimpinan dan Komunikasi Pengaruhnya Terhadap Kepuasan Kerja Pegawai Dinas Kepemudaan dan Olahraga Provinsi Sulawei Selatan - Nurjaya Nurjaya; Megawhati Artiyany; Sadariah Sadariah; M. Farid Wijaya Daud (Journal of Business and Economics Research (JBE), 2022)
The aim of this research is to prove the influence of leadership and communication on employee job satisfaction at the Youth and Sports Office of South Sulawesi Province, either partially or simultaneously. The research method used is a quantitative method with a sample of 55 people from a population of 120 people with the Accidental Sampling technique. The results showed: (1) Leadership has a significant effect on employee job satisfaction with the results of the T-test > T-table and a significant value of 0.002 <0.05. (2) Communication has a significant effect on employee job satisfaction with the results of the T-test > T-table test and a significant value of 0.021 <0.05. (3) Leadership and communication simultaneously have a significant effect on employee job satisfaction with the results of the calculated F test > F table test and a significant value of 0.001 <0.05